Solving linear regression without skewness of the residuals' distribution. Issue 8 (3rd August 2021) - Ricker, Martin
Abstract: Linear ordinary least squares (OLS) regression assumes an unskewed distribution of the residuals for correct inference and prediction. A proof is given that for Manly's exponential transformation of the dependent variable, there is always at least one solution for λ, such that the skewness of the standardized residuals' distribution is zero. A computer code in Mathematica, together with an illustrative example, are provided. Generalized linear models are discussed briefly in comparison.